Cytochemical detection of peroxisomes in light and electron microscopy with 3,3′-diaminobenzidine - Fahimi, H. Dariush (Peroxisomes, 2017)
Peroxisomes are ubiquitous dynamic and multifunctional organelles that contribute to numerous anabolic and catabolic pathways, being essential for human health and development. Their best known functions include the oxidation of fatty acids and metabolism of hydrogen peroxide with catalase as a marker enzyme. Indeed, historically, it was the cytochemical staining of catalase in many different cells and tissues that revealed the ubiquitous presence of peroxisomes in almost all animal and plant cells. In this chapter, the method for cytochemical staining of catalase with the alkaline 3, 3′-diaminobenzidine (DAB) is described. Since aldehyde fixation is a prerequisite for staining of catalase with DAB, a method for perfusion fixation of rat liver with glutaraldehyde is presented prior to the cytochemical staining method and the subsequent tissue processing for light and electron microscopy.
Gesehen am 14.11.2018